Multimodal treatment of unresectable hepatocellular carcinoma to achieve complete response results in improved survival. Issue 5 (May 2015) - Newell, Pippa H.; Wu, YingXing; Hoen, Helena; Uppal, Richa; Thiesing, John Tyler; Sasadeusz, Kevin; Cassera, Maria A.; Wolf, Ronald F.; Hansen, Paul; Hammill, Chet W
Abstract: Introduction: With technological advances, questions arise regarding how to best fit newer treatment modalities, such as transarterial therapies, into the treatment algorithm for patients with hepatocellular carcinoma (HCC). Methods: Between 2005 and 2011, 128 patients initially treated with transarterial radioembolization or chemoembolization using drugeluting beads were identified. The response was graded retrospectively. Toxicity was measured 1, 3, and 6 months after the first and last treatments. Results: Sixtyfive patients (53%) were advanced stage. Twenty patients (16%) had an initial complete response, but with additional treatments, this was increased to 46 (36%). Patients with a complete response as their best response to treatment had a median survival [95% confidence interval (CI)] of 5.77 (2.58, upper limit not yet reached) years, significantly longer than those whose best response was a partial response, 1.22 (0.84, 2.06) years and those with stable disease as their best response, 0.34 (0.29, 0.67) years. Repeated treatments did not increase toxicity. Discussion: This retrospective review of patients treated for intermediate and advanced stage HCC revealed a significant survival advantage in patients who achieved a complete response. These data support use of a multimodality approach to intermediate and advanced stage HCC, combining liverdirected treatments as necessary to achieve a complete response.